2017
DOI: 10.1039/c7nr02976d
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-activated transport of ions through single-walled carbon nanotubes

Abstract: Ionic transport through single-walled carbon nanotubes (SWCNTs) is promising for many applications but remains both experimentally challenging and highly debated. Here we report ionic current measurements through microfluidic devices containing one or several SWCNTs of diameter of 1.2 to 2 nm unexpectedly showing a linear or a voltage-activated I-V dependence. Transition from an activated to a linear behavior, and stochastic fluctuations between different current levels were notably observed. For linear device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…Later Secchi et al [5] showed that the CNT conductance at low c s varies with c s and the pH of the solution and extracted an exponent α = 1/3. A similar observation has been made recently by Yazda et al [7], but with a different power law. The theoretical explanation proposed in the literature is charge regulation [5,25], i.e.…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Later Secchi et al [5] showed that the CNT conductance at low c s varies with c s and the pH of the solution and extracted an exponent α = 1/3. A similar observation has been made recently by Yazda et al [7], but with a different power law. The theoretical explanation proposed in the literature is charge regulation [5,25], i.e.…”
Section: Introductionsupporting
confidence: 88%
“…Experiments on single-walled CNTs have been performed recently for radii between 0.6 and 1 nm and using KCl [7]. For those that showed a linear I − V curve, the conductance was measured as a function of c s .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CNTs have recently been regarded as interesting candidates for highly selective and permeable solid-state ion channels, mimicking biological ion channels, due to their unique structure. Recent data, demonstrating the electrophoretic transport of ions through CNTs [53] support and strengthen our hypothesis that electrochemical interactions, due to the generation of ionic currents, could take place between cell membranes and electro-conductive CNTs. Taken together, our results show, for the first time, that electroconductive MWCNTs can change microglia phenotype and function, without been cytotoxic.…”
Section: Discussionmentioning
confidence: 63%